Hepatoprotective activity of 1,2,4-triazole-3-thione derivatives, which contains on c5-atomic carbon hydroxy(phenyl)methyl dependent - A. M. Rud; A. G. Kaplaushenko; E. S. Pruglo; Yu. S. Frolova (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Relevance of pharmaceuticals with high efficiency and low cost for the prevention and treatment of diseases of the digestive system is unquestionable. It would be appropriate to mention that we carried out an analysis of a number of studies in which hepatoprotective effects of 1,2,4-triazole derivatives were carried out, and showed high hepatoprotective effects. Therefore, the search for hepatoprotectors in the series of 1,2,4-triazole derivatives has not only theoretical but also practical significance. The aim of our work was to study the first synthesized derivatives of 1,2,4-triazole-3-thione, which was containing substituents on C5 by carbon atom in conditions of tetrachormethane hepatitis. To model toxic hepatitis, a hepatotoxic xenobiotic, carbon tetrachloride, was used. The study of biochemical indicators of liver status was carried out 24 hours after the last injection of carbon tetrachloride. The ability of the test compounds to restore the integrity of hepatocyte membranes was determined by the anti-cytolytic effect (decrease in the activity of Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST)). According to the results of the study, it was found that among 43 test compounds, 5 are able to prevent survival at 85.71%. Thus, among the substances studied, compound 2c, which contributed 85.71% of the survival of the experimental animals and decrease 33.43% in ALT and 34.33% in AST. In this case, a very weak inverse dependence of the above indices was observed (r = -0.31). Some regularities of the chemical structure of the hepatoprotective action of 1,2,4-triazole derivatives have been established, so the survival of the experimental animals decreased with the introduction of a phenyl substituent of the starting thiones with N4.